The central nervous system : structure and function - Brodal, Per (OUP E-Books., 2004)
This textbook provides knowledge and understanding of neuroscience as a basis for clinical thinking. The strong emphasis on linking basic sciences with their clinical application has implications for the choices of which topics to treat in depth and which to treat more summarily - making this different from most other neuroscience textbooks. The book provides clear descriptions of brain structures and relates them to their functional properties by incorporating data ranging from molecular biology to clinical neurology and psychiatry. The focus is on fostering understanding of how the brain works rather than on the memorization of many details.